STUDI ANALISA PENGHEMATAN ENERGI DI GEDUNG DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BADUNG - Sastrawan, I Wayan; Dyana Arjana, I Gede; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
Today, excessive use of electrical energy will certainly cause energy wastage, given the energy crisis that has hit all countries, the government must have made efforts to save energy use. In 2019, the energy consumption of the Badung Regency DPRD Building was 41.8 kWh/m2 month, when compared to the Minister of Energy and Mineral Resources Regulation No. 13 on an Air-conditioned Building, which was 14 kWh/m2 month, the DPRD Building was included in the wasteful category. Based on these problems, efforts are needed to evaluate the use of electrical energy in the DPRD Building by means of energy conservation. The purpose of the study was to identify the potential for saving electrical energy that can be applied to the Badung Regency DPRD Building. The research method uses a descriptive quantitative approach where the results of calculations and measurements are then described and compared with Indonesian national standards on energy conservation. The results of the research show that the potential for saving electrical energy can be done by replacing the standard Split AC into a low watt AC where the electrical energy savings are obtained by 11.62% or a budget savings of Rp. 21,068,468.-